Polaris - Northrop, Michael (Scholastic Press, 2017)
"In the 1830s Owen Ward is cabin boy on the "Polaris," a ship on a voyage of scientific exploration, when illness and a mutiny off the coast of Brazil cause the adult crew to abandon the ship, leaving the handful of young cabin attendants and deckhands behind. The young seafarers are determined to bring their ship to safety, but when one of them disappears they begin to suspect that there is something deadly on board with them"--